Evaluation of empirical relationships to estimate the hydraulic conductivity of borehole soil samples. Issue 4 (2nd October 2022) - Chandel, Abhishish; Shankar, Vijay
ABSTRACT: Hydraulic conductivity is a vital hydraulic property of porous media that influences the movement of water and the transport of dissolved contaminants. The present study investigates the influence of key parameters namely, grain size and porosity on the hydraulic conductivity of the borehole soil samples. Further, the applicability of various porosity functions, nine existing empirical relationships, and the developed statistical model was assessed using experimentally measured values. Experimental investigations show that an increase in the grain size and porosity values results in an increase in the value of hydraulic conductivity. Porosity function corresponding to the Kozeny-Carman relationship provides the best fit with the measured hydraulic conductivity. The hydraulic conductivity computed using the Kozeny-Carman relationship indicates close agreement with the measured values followed by Beyer, Hazen, and Alyamani and Sen relationships while other relationships underestimate the hydraulic conductivity of the considered borehole soil samples. The values obtained using the developed model indicate better agreement as compared to those based on the empirical relationships, with the measured values of hydraulic conductivity. The reasonable values of SI, Cc, RMSE, and MAE i.e., 0.012, 0.984, 0.001, and 0.001 respectively, postulate substantial performance of the developed model in computing hydraulic conductivity.